Taut and click: an unusual left ventricular false tendon. (20th June 2016) - Hussain, Arif; Anderson, Robert H.; Dhillon, Santokh S.
Abstract: A case of an asymptomatic child presenting with persistent systolic ejection click and found to have an unusual left ventricular false tendon attached to aortic valve that has not been described previously and may be responsible for the click.